Energy-aware combinatorial resource scheduling model for cloud computing - Öner, Erbil (My University, 2022)
Considering the increasing demand for cloud computing and the financial and environmental impact of the increasing energy consumption trend of data centers, improving energy efficiency is vital for cloud service providers. One of the problems to be solved in order to improve energy efficiency in clouds is the problem of scheduling virtual machines on physical servers. In this study, a virtual machine scheduling problem is presented utilizing the combinatorial auction mechanism that takes energy consumption into account. In this model, virtual machine resources will be allocated to users for a certain period of time. Bidders include the virtual machine resource information and time period constraints in their bids. Also, as it is a model based on the multi-unit combinatorial auction, bidders can specify substitution and complementarity between virtual machine resources in their bids via the provided bidding language. The study also presents the mathematical formulation of the model and the outcome determination problem designed to determine which bidders' resources are to be scheduled. An integer program is formulated for the outcome determination problem, which is proven to belong to the NP-Hard problem set. Four different heuristic approaches are proposed to solve this problem. As a result of extensive experiments conducted with the developed synthetic test generator, it has been demonstrated that the proposed methods achieve better results in shorter time periods compared to the state-of-the-art mixed-integer programming solvers.

Günümüzde bulut bilişime yönelik artan talebin ve veri merkezlerinin artan enerji tüketiminin finansal ve çevresel etkileri göz önüne alındığında, bulut hizmeti sağlayıcıları için enerji verimliliğinin artırılması hayati önem taşımaktadır. Bulut bilişimde enerji verimliliğini artırmak için çözülmesi gereken problemlerden biri de sanal makinelerin fiziksel sunucular üzerinde zamanlanması problemidir. Bu çalışmada, enerji tüketimini hesaba katan çoklu birleşimsel müzayede modeline dayalı bir sanal makine zamanlama problemi ele alınmaktadır. Modelde sanal makine kaynakları belirli bir zaman aralığı için kullanıcılara tahsis edilmektedir. Teklif sahipleri, tekliflerinde istedikleri sanal makine kaynak bilgilerini ve süre kısıtlamalarını belirtirler. Ayrıca teklif sahipleri, çoklu birleşimsel müzayede modeliyle beraber sağlanan teklif dili aracılığıyla sanal makine kaynakları arasında ikame ve tamamlayıcılık bilgisini tekliflerine ekleyebilirler. Çalışma ayrıca, modelin matematiksel formülasyonunu ve hangi teklif sahibine ait sanal makine kaynaklarının yerleştirileceğini belirlemek için tasarlanan sonuç belirleme problemini sunmaktadır. NP-Zor problem kümesine ait olduğu kanıtlanmış olan sonuç belirleme problemi için bir doğrusal tam sayı formüle edilmiştir. Çalışmada bu problemi çözmek için dört farklı sezgisel yaklaşım önerilmiştir. Geliştirilen sentetik test üreteci ile yapılan kapsamlı deneyler sonucunda, önerilen yöntemlerin karışık tam sayı çözücülerine kıyasla daha kısa sürelerde daha iyi sonuçlara ulaştığı ortaya konmuştur.
Keywords: auction; Bilgisayar mühendisliği; birleşimsel optimizasyon; cloud computing; combinatorial optimization; Computer engineering; heuristic algorithms; kaynak zamanlama; müzayede; optimizasyon; optimization; resource scheduling bulut bilişim; scheduling; sezgisel algoritmalar; zamanlama